#NEVERAGAIN: Framing in Community and National News Coverage of the Parkland Mass Shootings. (21st April 2022) - Holody, Kyle J.; Shaughnessy, Brittany
ABSTRACT: This study examined the salience and valence of frames in community and national newspaper coverage of the 2018 Parkland shootings, after which several survivors became well-known activists. Of the most common frames found in previous coverage of mass shootings (gun control, popular culture, school safety), only gun control was prominent following the shootings in Parkland. Newer frames (partisan divide, activism, mental health) instead followed gun control in popularity, likely because these were utilized by the activist Parkland survivors themselves. With a few important exceptions (e.g., community newspapers used community change, law responsibility, and family responsibility more; national used gun control, activism, and partisan divide more), local and community newspapers were similar in their use of frames. Perhaps most importantly, the findings indicate the survivors' activism seemed to disrupt the "settling" of news coverage into well-established frames for mass shootings. This suggests the ongoing conversation about mass shootings remains complicated and more dependent on shootings' specific circumstances than may have been previously assumed.